Causal Model of Aggression based on Personality Traits, Early Maladaptive Schema and Aggression: Mediating Role of Emotion Regulation Strategies - Shila Mohseni; Majid Barzegar; Azarmidokht Rezaei; Hossein Baghooli (روانشناسی بالینی و شخصیت)
Introduction: Aggression is an abnormal phenomenon that is notably prevalent during adolescence, with various factors contributing to its occurrence. The aim of this study was to investigate the mediating role of cognitive emotion regulation strategies in the relationship between early dysfunctional schemas, personality traits, and aggression.Method: The research design employed correlational analysis and structural equation modeling. The statistical population of the study comprised all second-year high school students in Yasuj during the 2019-2020 academic year. A total of 340 students were selected using multi-stage cluster random sampling. Four questionnaires were utilized to collect data: Young's Early Maladaptive Schemas Short Form (SQ-SF), the Five Factor Model of Personality (NEO), the Cognitive Emotion Regulation Questionnaire (CERQ), and the Aggression Questionnaire (AQ). Data analysis was conducted using Pearson correlation methods and structural equation modeling, employing SPSS and AMOS software. Results: The results indicated that, among the personality traits, responsibility, agreeableness, extraversion, and flexibility had a negative and significant impact on maladaptive emotion regulation strategies. Conversely, extraversion and flexibility demonstrated a positive and significant influence on adaptive emotion regulation strategies. Additionally, the schemas of emotional deprivation, abandonment, distrust, and emotional inhibition had a positive and significant impact on maladaptive emotion regulation strategies. Conversely, the schemas of abandonment, deficiency, shame, and entitlement negatively affected adaptive emotion regulation strategies. In addition, the personality trait of agreeableness had a negative direct effect, while the schemas of abandonment, social isolation, failure, emotional inhibition, and entitlement had a positive direct effect on aggression. Finally, among the dimensions of personality traits—responsibility, agreeableness, extraversion, and flexibility—and the dimensions of early dysfunctional schemas—emotional deprivation, abandonment, distrust, shame and inferiority, emotional inhibition, and entitlement—these factors can indirectly influence aggression through cognitive emotion regulation strategies.Discussion and conclusion: In summary, it can be concluded that the interplay of personality trait variables, early dysfunctional schemas, and cognitive emotion regulation strategies significantly contributes to predicting adolescent aggression. The findings of this study can be valuable for school counselors and psychologists in addressing issues related to aggression and emotional dysregulation.